Can a New Organization Mitigate Conflicts Among Multiple Institutions Managing a World Heritage Site? Case of Borobudur Tourism Authority Board - Mallalahi, Nurul Hasmy; Yamada, Kyohei (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
This paper examines whether and to what extent a newly established public organization can facilitate coordination among existing organizations in a world heritage site by focusing on the Borobudur Tourism Authority Board (BOB). It was established in 2017 by the Indonesian government to reduce conflicts among the multiple organizations managing Borobudur World Heritage Site and to provide one-stop services in the area. The paper investigates how effective this newly created organization has been in achieving these goals by utilizing in-depth interviews of public officials and a survey of tourism service providers in the Borobudur area. Major findings include: (1) business conditions as perceived by service providers somewhat improved after the establishment of BOB; (2) however, existing authorities managing the Borobudur area bypass BOB as a coordinator; and (3) a result, conflicts among organizations involved in the Borobudur area remain.